(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The aim of the research is to determine the role of the control environment in the insurance industry in the National Insurance Company, and through studying and analyzing the control environment and formulating a number of questions expressing the problem of this research, in the National Insurance Company, the research sample, and the questionnaire was adopted as a main tool for collecting information in this research. It was distributed to (94) employees in the company, and the process of analyzing the results was carried out through the ready-made statistical programs (AMOS, V24, EXCEL, SPSS), which indicated the final results that it reached is the existence of a correlation and the impact of the control environment in the insurance industry in the research sample company And it was also recommended to adopt the concepts of the control environment because of its great role in raising the performance of the insurance industry.